2017 IEEE International Ultrasonics Symposium (IUS) 2017
DOI: 10.1109/ultsym.2017.8092343
|View full text |Cite
|
Sign up to set email alerts
|

Acoustical characterisation of carbon nanotube-loaded polydimethylsiloxane used for optical ultrasound generation

Abstract: Abstract-An optical ultrasound generator was used to perform broadband (2 − 35 MHz) acoustical characterisation measurements of a nanocomposite comprising carbon nanotubes (CNT) and polydimethylsiloxane (PDMS), a composite that is commonly used as optical ultrasound generator. Samples consisting of either pure PDMS or CNT-loaded PDMS were characterised to determine the influence of CNTs on the speed of sound and power-law acoustic attenuation parameters. A small weight fraction (< 1.8%) of added CNTs was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The CNT-PDMS film exhibits low frequency dependent attenuation over the majority of the frequency range relevant to the current study; e.g. a 100 μm film attenuates frequencies up to 22 MHz by less than 1.7dB [13]. The attenuation of the photoacoustic wave as it propagates through the CNT-PDMS film is thus negligible.…”
Section: A Optical Ultrasound Generationmentioning
confidence: 89%
“…The CNT-PDMS film exhibits low frequency dependent attenuation over the majority of the frequency range relevant to the current study; e.g. a 100 μm film attenuates frequencies up to 22 MHz by less than 1.7dB [13]. The attenuation of the photoacoustic wave as it propagates through the CNT-PDMS film is thus negligible.…”
Section: A Optical Ultrasound Generationmentioning
confidence: 89%
“…The lower sound pressure at the 0.9 µm thin sample was caused by the fact that more transmission of the laser beam takes place, in this case a thin layer emits higher frequencies ultrasonic waves. [ 11,18,61 ] The relation of layer thicknesses with frequency ranges can be showed with the 32.2 µm thick sample, where the spectrum of 6.7 MHz differs significantly from the others ranging from 9.0 up to 9.7 MHz. [ 11,18,61 ] The sound pressure measured with the 32.2 µm thick layer (Figure 8b) is not significantly higher (3.2 MPa), since the attenuation of the ultrasound pressure in thicker layers becomes stronger than within thinner layers.…”
Section: Ultrasound Pressure Measurementsmentioning
confidence: 99%
“…[ 11,18,61 ] The relation of layer thicknesses with frequency ranges can be showed with the 32.2 µm thick sample, where the spectrum of 6.7 MHz differs significantly from the others ranging from 9.0 up to 9.7 MHz. [ 11,18,61 ] The sound pressure measured with the 32.2 µm thick layer (Figure 8b) is not significantly higher (3.2 MPa), since the attenuation of the ultrasound pressure in thicker layers becomes stronger than within thinner layers. [ 18 ] Poduval et al observed and describes similar effects, which explain the lower sound pressures at 0.9 and 32.2 µm.…”
Section: Ultrasound Pressure Measurementsmentioning
confidence: 99%
“…The bandwidth of this wave depends on the temporal characteristics of the excitation light. In general, the bandwidth can be increased by decreasing the duration of excitation light pulses; however, in practice, these increases are limited by frequency-dependent ultrasound attenuation within the coating ( 10 ) and within blood and vascular tissue ( 11 ). To achieve efficient optical-US transduction, a material with a high optical absorption coefficient and a high thermal expansion coefficient is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…These high pressures enable high imaging penetration depths, and the broad bandwidths give rise to high axial resolution. A small coating thickness can be important to minimize acoustic attenuation within nanocomposite materials ( 10 ). To this end, several methods have been explored for depositing nanocomposite materials onto the distal surface of the fiber optic transducer, including spin-coating ( 17 ), electrospinning ( 18 ), and dip-coating ( 15 ).…”
Section: Introductionmentioning
confidence: 99%